Impossible subjects : illegal aliens and the making of modern America - Ngai, Mae M. (Politics and society in twentieth-century America., 2014)
This book traces the origins of the "illegal alien" in American law and society, explaining why and how illegal migration became the central problem in U.S. immigration policy - a process that profoundly shaped ideas and practices about citizenship, race, and state authority in the twentieth century. The author offers a close reading of the legal regime of restriction that commenced in the 1920s - its statutory architecture, judicial genealogies, administrative enforcement, differential treatment of European and non-European migrants, and its long-term effects.